Studies on Preparation and Storage of Osmotic Dehydrated Wild Pear (Pyrus serotina) - Dhiman, Anju Kumari; Devi, Lucky; Attri, Surekha; Sharma, Anshu (International Journal of Bio-resource and Stress Management, 2016)
Studies were conducted during the months of October–December in 2011 and January-April in 2012 at the Department of Food Science and Technology, Dr. Yashwant Singh Parmar, University of Horticulture and Forestry, Nauni, Solan (HP). Process for preparation of wild pear halves using osmotic dehydration was standardized. Fully ripe wild fruits of pear were peeled and cut into halves. The halves were soaked in 50 °Brix (Recipe 1), 60 °Brix (Recipe 2), 70 °Brix (Recipe 3) and 80 °Brix (Recipe 4) sugar solutions, respectively. After 24 h soaking in sugar solutions, quick washing, blotting and then cabinet drying at 55–60 °C for 5−6 h was done. The dried products were packed in polyethylene pouches and stored at ambient condition for six months. The physico-chemical, microbial and sensory changes were analyzed at an interval of 0, 3 and 6 months. The osmo-dried wild pear halves prepared after using water blanching for 5 minutes+1.0% citric acid dip for 30 minutes was found better in respect to colour, texture, taste and overall acceptability among various treatments. Storage studies indicated that there was significant decrease in moisture content, titratable acidity, ascorbic acid, total phenols, sensory quality scores and increase in TSS and TSS: acid ratio of wild pear halves. The stored osmo-dried wild pear halves were found microbiologically safe and sensorily acceptable up to six months of storage at ambient condition.